Frequency of occurrence of urticaria after the administration of atracurium - Kumar, Ajay; Jain, Anil Kumar; Gupta, Sanjeev (International Journal of Research in Dermatology, 2016)
Background: Atracurium is a non-depolarizing neuromuscular blocking agent generally used for short and intermediate duration surgical procedures. Atracurium may cause urticaria due to direct, non-immunological release of histamine from mast cells.Though cutaneous changes due to histamine release by atracurium have been reported in various studies these changes were not clinically evaluated by dermatologists. The aim of the study was to assess the frequency of occurrence of urticaria after the administration of atracurium in the conventional dose schedule. Haemodynamic changes in pulse rate and mean arterial pressure (MAP) were also evaluated. Methods: 60 patients aged 12 years and above, undergoing various elective surgical procedures were enrolled in the study. Atracurium was administered in a dose of 0.6 mg/kg body weight after induction. Cutaneous changes if any including erythema and urticarial weals were observed during the intraoperative phase and images recorded for further evaluation by the investigators including dermatologists. Baseline values of pulse rate and MAP as well as values 1 min, 3 min and 5 min after the administration of atracurium were recorded. Results: None of the patients developed urticarial weals after the administration of atracurium. Five patients (8.33%) developed erythema during the intraoperative period. Changes in pulse rate and MAP were found to be significant. Conclusions: Atracurium in conventional dosage is not associated with urticaria. Haemodynamic changes after the administration of atracurium are significant.